Security and privacy issues and requirements for healthcare cloud computing - Gavrilov, Goce; Trajkovik, Vladimir (My University, 2012)
Information technology is increasingly used in healthcare with the goal to improve and enhance medical services and to reduce costs. One of the areas with greatest needs having available information at the right moment and with high accuracy is healthcare. With the widespread use of electronic health record (EHR), building a secure EHR sharing environment has attracted a lot of attention in both healthcare industry and academic community. Cloud computing paradigm is one of the popular health IT infrastructure for facilitating EHR sharing and EHR integration. Healthcare clouds offer new possibilities, such as easy and ubiquitous access to medical data, and opportunities for new business models. However, they also bear new risks and raise challenges with respect to security and privacy aspects. Ensuring the security and privacy is a major factor in the cloud computing environment. In this paper, we will present current state of the art research in this field. We focused of several shortcomings of current healthcare solutions and standards, particularly for platform security, privacy aspect and requirements which is a crucial aspect for the overall security of healthcare IT systems.
Keywords: cloud computing, electronic health record (EHR), privacy, security